Nutrients mineralization from sludge amended acid soil in Thailand - Bregnhoj, , Henrik; Christian TjeIl, Jens (Malaysian Journal of Science, 2004)
An appropriate sludge application depends on the rate of the mineralization process which will release nutrients to the cropland. This study was aimed at investigating the nitrogen and phosphorus mineralization from two sludges, septage and sewage mixed into an agricultural acid soil. The research design was multiple independent variables with two types of sludge, three sludge application rates, two levels of lime addition, and four incubation times under aerobic condition. A non-linear least square regression was used for prediction of mineralization parameters. Within six weeks, only 26% and 17% of nitrogen were mineralized in the soil applied with septage sludge and sewage sludge, respectively. The application of septage sludge gave higher potentially mineralizable nitrogen (No) 247 mg N/kg with mineralization rate constant (k) 0.046 week-1 but slightly lower phosphorus mineralization rate (48%) than that of the sewage sludge (51%). Nutrients mineralization increased with an increasing sludge application rate and incubation time. Other factor influencing nitrogen mineralization was lime addition, while phosphorus mineralization depended on sludge type. After six weeks of incubation, the soil had reached neutral pH and added 3-4% organic matter. It contained higher total heavy metals but still under the allowable metals concentrations, and phytotoxic threshold for plant growth.